1992
DOI: 10.2334/josnusd1959.34.172
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyproline and Total Protein Levels in Gingiva and Gingival Crevicular Fluid in Periodontally Healthy Human Subjects.

Abstract: Age is known to be one of the factors which affect the rate of collagen and protein turnover in the connective tissues of the periodontium. The aim of the present study was to determine the levels of hydroxyproline (Hyp) and total protein in both the gingiva and gingival crevicular fluid (GCF) of periodontally healthy human subjects of two different age groups. The subjects of the young group were selected from among patients scheduled for extraction of upper and lower first or second premolars for orthodontic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…In contrast, no differences in total GCF protein content were seen. 9 The lack of significant changes in total GCF protein content is consistent with the hypothesis that the amount of GCF, ie, the flow rate, is not sensitive to the different growth phases. Therefore, the GCF volume would also not be expected to be influenced by the pubertal growth phase.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In contrast, no differences in total GCF protein content were seen. 9 The lack of significant changes in total GCF protein content is consistent with the hypothesis that the amount of GCF, ie, the flow rate, is not sensitive to the different growth phases. Therefore, the GCF volume would also not be expected to be influenced by the pubertal growth phase.…”
Section: Discussionsupporting
confidence: 73%
“…Although not using any method for precise assessment of the individual growth phases, a previous study 9 reported greater gingival total protein content in growing subjects as compared with an older group. In contrast, no differences in total GCF protein content were seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zymography evidenced differences between healthy and diseased subjects. Akalin et al (1992) 9) found that Hyp levels in gingival tissue and GCF from periodontally healthy human subjects of different age groups were higher in a younger group than in an older one.…”
Section: Resultsmentioning
confidence: 99%
“…Collagenases are associated with tissue destruction in periodontal disease; they degrade collagen and are also present in GCF, saliva and gingival tissue 7,8) . Since hydroxyproline (Hyp) is a specific amino acid of collagen, its detection in GCF is therefore considered a sign of destruction of gingival connective tissue 9) .…”
Section: Introductionmentioning
confidence: 99%